2021
DOI: 10.1146/annurev-marine-040220-101608
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Optimism: Moving Beyond the Obituaries in Marine Conservation

Abstract: While the ocean has suffered many losses, there is increasing evidence that important progress is being made in marine conservation. Examples include striking recoveries of once-threatened species, increasing rates of protection of marine habitats, more sustainably managed fisheries and aquaculture, reductions in some forms of pollution, accelerating restoration of degraded habitats, and use of the ocean and its habitats to sequester carbon and provide clean energy. Many of these achievements have multiple ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 145 publications
0
28
0
1
Order By: Relevance
“…The second is the wider emergence of “blue economy” discourses, emphasizing the economic opportunities that the ocean and ocean‐based activities offer (Voyer et al, 2018). Thirdly, this interest in the mitigation potential of the ocean is part of a shift in “ocean optimism” about progress in ocean conservation (Knowlton, 2021). The fourth is the growing interest in “nature‐based solutions” (NBS) of conserving and restoring ecosystems that provide benefits for climate, biodiversity and other societal goals (Griscom et al, 2017).…”
Section: Agency In Mobilizing the Political Ocean‐climate Bandwagonmentioning
confidence: 99%
“…The second is the wider emergence of “blue economy” discourses, emphasizing the economic opportunities that the ocean and ocean‐based activities offer (Voyer et al, 2018). Thirdly, this interest in the mitigation potential of the ocean is part of a shift in “ocean optimism” about progress in ocean conservation (Knowlton, 2021). The fourth is the growing interest in “nature‐based solutions” (NBS) of conserving and restoring ecosystems that provide benefits for climate, biodiversity and other societal goals (Griscom et al, 2017).…”
Section: Agency In Mobilizing the Political Ocean‐climate Bandwagonmentioning
confidence: 99%
“…Beneath the surface, there have been notable conservation successes (e.g. Duarte et al, 2020; Knowlton, 2020), but overall, despite the grand pronouncements, it is fair to say we continue to increase extraction of resources and add more pollutants, discounting the damage to the ocean as minor problems or acceptable losses, against perceived ‘essential’ exploitative gain. The growing global population is increasingly used by sectors, such as fisheries, as justification of ever greater levels of exploitation at the clear sacrifice of nature (Steneck & Pauly, 2019).…”
Section: Why a Better More Precise And Updated Ocean Narrative Is Neededmentioning
confidence: 99%
“…A systemic view of the ocean can promote mutually beneficial solutions for reaching humanity's full potential within safe sustainable limits, whilst still achieving the goal of a healthy global ocean (Singh et al, 2018; Claudet et al, 2020a). This is not without precedent, and numerous examples of success in conservation coupled with sustainable management of marine living resources to the benefit of both industry and local communities give grounds for ocean optimism (Knowlton, 2020).…”
Section: Resetting the Ocean Narrative Post‐covid‐19mentioning
confidence: 99%
“…The status assessment of fishery resources revealed that the fraction of fish stocks that are within biologically sustainable levels decreased from 90%, in 1974, to 65.8% in 2017 [6]. In contrast, recent studies argue that some fishing stocks are gradually recovering in different parts of the world [7], especially in regions where there are effective fisheries management [8]. Although these recent findings show positive global scenarios [9], overfishing is responsible for substantially modifying the abundance and biomass patterns of species and decreasing the body size of individuals in a population [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%